Efektivitas Layanan Bimbingan Kelompok Teknik Cinema Therapy Untuk Menurunkan Prokrastinasi Akademik Siswa Kelas XI SMA - Intan Lestari; MA. Primaningrum Dian; Ismah Ismah (Journal of Society Counseling, 2026)
This study examines the effectiveness of group guidance using cinema therapy to reduce academic procrastination at SMA Negeri 1 Kendal. This quantitative pre-experimental research utilized Likert-scale questionnaires. Out of 426 students (population). 62% scored low, while 27% required attention. A sample of 7 students underwent four cinema therapy sessions. Results showed total procrastination scores decreased from 65% (pre-test) to 48% (post-test), a 17% reduction, with task initiation dropping most significantly by 31%. Since Shapiro-Wilk normality tests indicated a non-normal data distribution (p=0.008), the Wilcoxon Signed Ranks Test was applied. It revealed a significant difference (Z=-2.371, p=0.018<0.05), rejecting H0. The intervention successfully fostered behavioral changes, dismantling ego defense mechanisms through self-projection and emotional catharsis. In conclusion, group guidance using cinema therapy is effective in reducing academic procrastination among students at SMA Negeri 1 Kendal.